A Nutrition Behaviour Change Intervention Delivered Through Women's Self-Help Groups in India Is Protective Against Depression and Reduces Time Spent in Market Work. (7th June 2021) - Gupta, Shivani; Scott, Samuel; Kumar, Neha; Raghunathan, Kalyani; Thai, Giang; Quisumbing, Agnes; Menon, Purnima
Abstract: Objectives: Women's self-help groups (SHGs), which operate at large scale in India, are an important platform for delivering behaviour change communication (BCC) and social support interventions to rural women. Little is known about how such group-based interventions affect women's mental health and time use. Methods: The Women Improving Nutrition through Group-based Strategies (WINGS) study was a quasi-experimental impact evaluation, comparing 16 blocks (8 matched pairs) with SHG formation support; 8 blocks received a 3-year nutrition intervention (NI) with BCC topics such as nutrition, home-gardens and women's well-being, facilitated by a trained female volunteer; the other 8 received standard activities (STD) to support savings & livelihoods. We conducted repeated cross-sectional surveys of mother-child pairs in 2017–18 ( n = 1609) and 2019–20 ( n = 1841). We matched treatment groups over time and applied difference-in-difference (DID) regression models to estimate NI impacts. Outcomes assessed: (1) common mental disorder symptoms (CMD) (Self Reporting Questionnaire (SRQ) score, 8 or higher) and (2) time use, constructed using 24-hour recall data. Time indicators were the proportion of time spent on productive work (employed, agricultural work), reproductive work (cooking, caring for children etc.), and time spent on social-leisure activities (hobbies, socializing). Results: Overall, women were 25 years old with 5 years of education and worked 10.7 hours/day. CMD were reported by 17% of women. DID estimates showed that CMD prevalence doubled over time among women in STD areas but did not change in NI areas ( P < 0.01). Compared to STD areas, women in NI areas reported a larger decrease in time spent on productive work (DID: −5 percentage points (pp); P < 0.01) and larger increases in time spent on reproductive work (DID: +5 pp; P < 0.01) and on social-leisure activities (DID: +22 minutes, P < 0.01). Conclusions: A BCC intervention delivered through SHGs in rural India protected against a secular trend in declining mental health and shifted women's time from market work to domestic and social-leisure activities. These findings add to a growing evidence base on the effectiveness of group-based interventions to improve women's wellbeing in developing countries. Funding Sources: Bill & Melinda Gates Foundation.